INFLUENCE OF GENERATIVITY, EXPERIENCE EXPECTATION, AND MOTIVATION ON VISIT INTENTION AT SEPULUH NOPEMBER MUSEUM, SURABAYA - Nie, Jocelyn; Andajani, Erna; Widjaja, Fitri Novika; Ardiansyahmiraja, Bobby (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
This research analyzes the contradictory results of previous research. This research was conducted to understand the influence of generativity, experience expectations, and motivation on visit intention, with the Sepuluh Nopember Museum, Surabaya, as a case study. The methodology used is quantitative, with primary data from questionnaires and analysis using Structural Equation Modeling (SEM) through SmartPLS 4.0 software. The findings show that generativity positively and significantly influences experience expectations, motivation, and visit intention. Motivation also positively affects visit intention, and experience expectation affects motivation. However, there is no significant effect of experience expectation on visit intention. Based on this, experience expectations are not always a determinant of interest in visiting. It would be better to advise business owners in similar fields to focus more on creating visitor motivation and contributions to future generations so that interest in visiting can increase in the future